Examining the Career Construction Model of Adaptation Among Filipino Senior High School Students. (December 2022) - Ochoco, Marc Sherwin A.; Ty, Welison Evenston G.
Career development literature that tested the career construction model of adaptation has, thus far, examined adaptability resource as a mediator in the relationship between adaptive readiness and adaptation results; however, there remains a need to elaborate the links between adaptive resources, adapting response, and adaptation results. This research tested a path model among 331 Filipino senior high school students using hope, career adaptability, career engagement, and life satisfaction as measures of adaptive readiness, adaptability resources, adaptive response, and adaptation results, respectively. Analyses revealed a significant serial relationship from hope to life satisfaction through career adaptability and career engagement. Findings suggest that having career-related abilities may not be enough to promote well-being; rather proactive career behaviors may be taken as a route to a satisfying life. Implications on theory, research, and practice are discussed.